Синтез новых производных гексагидропиридазинов на основе 4-кетогексагидропиридазинов - Р. С. Вартанян; Ж. В. Казарян; М. А. Шейранян; Ш. П. Мамбреян; А. Г. Хачатрян (ՀՀ ԳԱԱ հրատ.)
С целью перехода к биологически активным соединениям осуществлен синтез 2-амино-5,5-бисметоксикарбонил-3-циано-4,5,6,7тетрагидрофуро/2,3-d/пиридазина и 4-амино-6,7-бисметоксикарбонил-5,6,7-тетрагидропиримидо /5',4':4,5/ фуро/2,3-d/пиридазина на основе ранее не описанного 1,2-бисметоксикарбонил-5-гидрокси-гексагидропиридазин-4-она. Իրականացվել է 2-ամինա-5,5-բիսմեթոքսիկարբոնիլ-3-ցիանո-4,5,6,7-տետրահիդրո¬ֆուրո /2,3-d/ պիրիդազինի և 4-ամինա-6,7-բիսմեթոքսիկարբոնիլ-5,6,7,8-տետրահիդրոպիրիմիդո/5’,4’:4,5/ֆուրո/2,3-d/պիրիդազինի սինթեզները նախկինում չնկարագրված 1,2-բիսմեթոքսիկարբոնիլ-5-հիդրոքսիհեքսահիդրոպիրիդազին-4-ոնի հիման վրա: Hexahydropyridazine derivatives, as piperidine azaanalogs, are interesting from two points of view – as new chemical entities and as new biologically active compounds. Hexahydropyridazine chemistry is practically undescribed area. It is not investigated, by the reason of absence of convenient methods of the synthesis of their functionalized derivatives in literature.
Keywords: Organic Chemistry